2021
DOI: 10.1002/tox.23329
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin mitigates potassium dichromate‐induced nephrotoxicity, cardiotoxicity and genotoxicity through modulation of Kim‐1/Nrf2 signaling pathways

Abstract: Environmental and occupational exposure to chromium compounds has become potential aetiologic agent for kidney disease with excessive generation of free radicals, apoptosis, and inflammatory. These pathophysiologic mechanisms of potassium dichromate (K2Cr2O7) have been well correlated with nephrotoxicity and cardiotoxicity. The cardioprotective and nephroprotective effects of Luteolin, a known potent antioxidant were evaluated in this study with 40 healthy rats in four experimental groups: Group A (normal sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…There were studies have demonstrated that Cr(Ⅵ) exposure could lead the downregulation of mRNA and protein expressions of Nrf2, NQO1, and HO-1 in a dose dependent manner ( Yang et al, 2021 ). However, antioxidants enhanced Nrf2 mediated antioxidant defense system to prevent Cr(Ⅵ)-induced cardiotoxicity, pulmonary toxicity, and nephrotoxicity in rats ( Lv et al, 2020 ; Awoyomi et al, 2021 ). Se, as a powerful antioxidant, has been shown to reduce the toxic damage caused by As or Cd by activating the Nrf2 pathway ( Zwolak, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…There were studies have demonstrated that Cr(Ⅵ) exposure could lead the downregulation of mRNA and protein expressions of Nrf2, NQO1, and HO-1 in a dose dependent manner ( Yang et al, 2021 ). However, antioxidants enhanced Nrf2 mediated antioxidant defense system to prevent Cr(Ⅵ)-induced cardiotoxicity, pulmonary toxicity, and nephrotoxicity in rats ( Lv et al, 2020 ; Awoyomi et al, 2021 ). Se, as a powerful antioxidant, has been shown to reduce the toxic damage caused by As or Cd by activating the Nrf2 pathway ( Zwolak, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, luteolin inhibited the reduction in Nfe212 and Homx1 mRNA expression in Pb-treated rats, and reduced the production of proinflammatory markers (TNF-α, IL-1β and NO) and apoptotic related proteins while upregulating the expression of antiapoptotic proteins [ 136 ]. Awoyomi et al [ 137 ] showed that the pre-treatment with Luteolin (100 and 200 mg/kg) reduced acute kidney injuries induced by potassium dichromate (K 2 Cr 2 O 7 ), at dose of 30 mg/kg, through anti-oxidantive and radical scavenging mechanisms. Luteolin reduced oxidative stress indicators, augmented anti-oxidant mechanisms and serum Nitric oxide level, lowered the expressions of injury molecule (Kim-1) and up-regulated the renal, nuclear factor erythroid 2-related factor 2 (Nrf2) [ 137 ].…”
Section: Renoprotective Effects Of Luteolin Against Nephrotoxic Subst...mentioning
confidence: 99%
“…Awoyomi et al [ 137 ] showed that the pre-treatment with Luteolin (100 and 200 mg/kg) reduced acute kidney injuries induced by potassium dichromate (K 2 Cr 2 O 7 ), at dose of 30 mg/kg, through anti-oxidantive and radical scavenging mechanisms. Luteolin reduced oxidative stress indicators, augmented anti-oxidant mechanisms and serum Nitric oxide level, lowered the expressions of injury molecule (Kim-1) and up-regulated the renal, nuclear factor erythroid 2-related factor 2 (Nrf2) [ 137 ].…”
Section: Renoprotective Effects Of Luteolin Against Nephrotoxic Subst...mentioning
confidence: 99%
“…The ability to scavenge free radicals may be one of the mechanisms of P. asiatica as a health food and traditional Chinese medicine, especially in its protective effect on various organs. Luteolin ( 2 ) scavenges free radicals to exert cardioprotective, nephroprotective, hepatoprotective, neuroprotective, and antigenotoxic effects. Polysaccharides from P. asiatica inhibit the production of superoxide, 1,1-diphenyl-2-picrylhydrazyl (DPPH), and hydroxyl radicals . In addition, acteoside ( 27 ) and isoacteoside ( 28 ) also can scavenge intracellular reactive oxygen species (ROS), peroxynitrite (ONOO – ), and DPPH free radicals to prevent lipid peroxidation. ,, Except for changes in ROS levels, apigenin ( 1 ) has not been found and reported on free radicals, so apigenin ( 1 ) is an antioxidant mainly through the regulation of oxidative enzyme activity.…”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%
“…Apigenin ( 1 ) acts as an antioxidant drug against the accumulation of ROS upon injury via the Nrf2 signaling pathway . Nrf2 signaling also mediates luteolin ( 2 ) to significantly improve oxidative stress and various tissue injuries, including heart, kidney, , liver, , brain, retina, arthrosis, ovary, and testis injuries . Furthermore, plantamajoside ( 25 ), acteoside ( 27 ), and isoacteoside ( 28 ) inhibit ROS in cells attributed to the activation of Nrf2 transcription, , as well as the increase of HO-1 expression and enzymatic antioxidants (SOD, CAT, GSH-Px, etc.)…”
Section: Biological Activities and Molecular Pharmacologymentioning
confidence: 99%